Thoughts about the connection between spatial development and sustainable landscape at the region of the Northern Great Plain - Kerékgyártó, Gábor (Acta Agraria Debreceniensis, 2012)
This paper tries to find connections between sustainable landscape and spatial development policy of the Northern Great Plain region on the basis of specific examples explained in scientific literature. Searching for the common roots of spatial development and sustainability the paper explains two interpretation of sustainability from the view point of landscape, than the most significant element of current landscape change, the polarization of landscapes, will be introduced. This trend in landscape change basically determines the direction of spatial development. This paper analyses the Northern Great Plain region form two different approaches. In the first grouping the region is exposed from the view point of landscape. In the second partitioning the area is divided into subject matters based on the principles of sustainability and polarization of landscape. This research – analysing development plans and strategies – considers the current situation and the tasks of the future within the subject matters.